Impaired heart rate variability one and six months post acute COVID-19. (3rd October 2022) - Lampsas, S; Oikonomou, E; Souvaliotis, N; Goliopoulou, A; Papamikroulis, G A; Anastasiou, A; Theofilis, P; Zakynthinos, G; Gialamas, I; Pantelidis, P; Gounaridi, M A; Tsatsaragkou, A; et al.
Abstract: Background: Long COVID-19 syndrome is an increasingly recognized problem. Post-infectious cardiac autonomic dysfunction is commonly reported. This study aims to evaluate autonomic dysfunction by means of Heart rate variability (HRV) on post-COVID-19 patients. Methods: Hospitalized patients for COVID-19 (either at the medical ward or Intensive Care Unit (ICU)) were followed up at 1 and 6 months after hospital discharge. Medical history and clinical information were collected. HRV was assessed by 24-hour ambulatory electrocardiography Holter, with the measure of the standard deviation of normal RR intervals in 24 h, ms (SDNN). The comparison was conducted with age and sex-matched non-COVID-19 controls. Results: Thirty-four patients hospitalized with COVID-19 (20.6% admitted in ICU) were examined 1-month and 6-months post-hospital discharge. SDNN was significantly (p<0.001) reduced in the COVID-19 group (111±23 ms) compared to the control subjects (152±24 ms) 1-month after discharge. Subgroup analysis between COVID-19 group revealed that ICU subjects presented significantly (p<0.001) reduced SDNN compared to the medical ward, respectively (83±20 ms vs. 118±17 ms). At 6-months, an improvement was noted at SDNN 24h (6-month: 133±24 vs. control: 151±24 ms, p=0.004; 1-month: 111±23 ms vs. 6-month: 133±24 ms, p<0.001). Also at 6-months, ICU subjects noted significantly (p=0.003) reduced SDNN 24h compared to medical ward subjects (107±17 ms vs. 140±20 ms). On the 6-months follow-up, 32% of the subjects had "long-COVID-19" symptoms. Subjects with long COVID-19 symptoms had low SDNN values ("long-COVID-19": 112±17 ms vs. non-"long-COVID-19": 142±20 ms, p=0.001) Conclusion: Patients hospitalized for COVID-19 have reduced SDNN, at one month post-hospital discharge which is improved at the six months follow-up. These findings emphasize the increased sympathetic drive activity in the post-acute COVID-19 phase and imply a link between autonomic dysfunction and long COVID-19. Funding Acknowledgement: Type of funding sources: None.